2022
DOI: 10.3390/genes13101780
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Diversity and the Divergence Time in Extant Primitive Mayfly, Siphluriscus chinensis Ulmer, 1920 Using the Mitochondrial Genome

Abstract: In this study, the mitochondrial (mt) genomes of Siphluriscus chinensis (Ephemeroptera: Siphluriscidae) were evaluated in specimens collected from two sites in China: Niutou Mountain, Zhejiang Province (S. chinensis NTS) and Leigong Mountain, Guizhou Province (S. chinensis LGS) and were successfully sequenced. The lengths of the mt genomes of S. chinensis NTS and S. chinensis LGS were 15,904 bp (ON729390) and 15,212 bp (ON729391), respectively. However, an in-depth comparison of the two mt genomes showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Both trees supported that Isonychiidae diverged next to Siphluriscidae, a result that was also supported by Cao et al and Xu et al in reconstructing the phylogenetic relationships of Ephemeroptera based on the 13 PCGs [76,109], but Baetidae was supported as the sister clade to other families of mayflies, excluding Siphluriscidae [24]. Teloganodidae was clustered with Baetidae, which was consistent with other research [26,57,76,77], but this result may have been caused by the long branch attraction. Both trees recovered the monophyly of Potamanthidae and suggested a relationship of Potamanthidae + (Ephemeridae + Polymitarcyidae), which was consistent with Wang et al [25].…”
Section: The Phylogeny Of Potamanthidaesupporting
confidence: 87%
See 2 more Smart Citations
“…Both trees supported that Isonychiidae diverged next to Siphluriscidae, a result that was also supported by Cao et al and Xu et al in reconstructing the phylogenetic relationships of Ephemeroptera based on the 13 PCGs [76,109], but Baetidae was supported as the sister clade to other families of mayflies, excluding Siphluriscidae [24]. Teloganodidae was clustered with Baetidae, which was consistent with other research [26,57,76,77], but this result may have been caused by the long branch attraction. Both trees recovered the monophyly of Potamanthidae and suggested a relationship of Potamanthidae + (Ephemeridae + Polymitarcyidae), which was consistent with Wang et al [25].…”
Section: The Phylogeny Of Potamanthidaesupporting
confidence: 87%
“…Thereafter, based on over 400 targeted genomic protein coding regions, Odgen et al suggested that Potamanthidae was the sister clade of all remaining burrowing mayflies [24], and this result was consistent with the work of Miller et al [14]. In recent years, Wang et al supported the phylogenetic relationship of Potamanthidae + (Ephemeridae + Polymitarcyidae), whereas Tong et al suggested the phylogenetic relationship of (Potamanthidae + Ephemeridae) + Polymitarcyidae [25,26]. Of note, most researchers have been involved in morphological studies and other aspects of Potamanthidae rather than molecular research [11,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Many tick species share great morphological similarities and therefore group into species complexes until differentiating characters can be described [ 22 ]. The mitochondrial genome (mitogenome) is a reliable marker for cryptic species identification, phylogenetic studies, and population genetics analysis, and has been widely used in animals [ 23 , 24 , 25 , 26 , 27 , 28 ], including in ticks [ 7 , 21 , 29 ]. In recent years, the number of sequenced mitogenomes of Ixodidae species has increased significantly, but the mitogenome studies on parasitic ticks of giant pandas have only been performed for three Haemaphysalis species [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are 38,874 described species of Cerambycidae (Coleoptera: Polyphaga) to date, according to the "Titan database about Cerambycidae" (http://titan.gbif.fr/sel_sous_famille.php, accessed on pha using PCGs, tRNA, and rRNA genes of mitochondrial genomes [28]. Additionally, mitochondrial genomes have also been used as molecular markers in the phylogeny of Mantodea [29,30], Phasmatodea [31,32], Archaeognatha [33], Ephemeroptera [34], etc., with remarkable results.…”
Section: Introductionmentioning
confidence: 99%